NEW PALEOMAGNETIC DATA ON THE SILURIAN AND DEVONIAN SEDIMENTARY ROCKS FROM PODOLIA, SW UKRAINE, AND KINEMATICS OF THE EAST EUROPEAN PLATFORM IN THE MIDDLE PALEOZOIC - V. G. Bakhmutov; I. B. Poliachenko (Геодинамика и тектонофизика)
Paleomagnetic data are the priority source of information for global paleotectonic reconstructions representing horizontal movements of the crustal blocks. Upon receipt of new paleomagnetic data, kinematic models of the East European platform in the Paleozoic are regularly revised and improved. The article presents results of the paleomagnetic study of sedimentary gray-colored and red beds of the Silurian and Lower Devonian sequences located in the Dniester river basin, Podolia region, SW Ukraine. The study covered 17 outcrops that are stratigraphically correlated with the Wenlock, Ludlow, Pridoli states of the Sillurian and the Lochkovian stage of the Devon. Over 400 samples of grey limestone, argillite, dolomite, red limestone and sandstone were analyzed, and two components of natural remnant magnetization (NRM) were revealed. The first component with SSW declination and negative inclination is revealed in the majority of the samples during AF- and T-magnetic cleaning. Its pole positions, that are calculated separately for each series, are trending to the Permian segment of the apparent polar wander path (APWP) published by Torsvik et al. [2012] for Baltica / Stable Europe. Considering its chemical origin, this NRM component is related to formation of authigenic minerals due to rock remagnetization. The second component is revealed only in some samples taken from the red beds (during thermal demagnetization in the range of unblocking temperatures from 590 to 690 °С) and in few samples of grey limestone (in AF fields from 30 to 70 mT or in the range of unblocking temperatures from 300 to 460 °С). This component has SW declination and positive inclination, goes to the origin of coordinates of the diagrams, and has all the indicators of primary magnetization of sediments. Calculated positions of the poles (0 ºS and 329 ºE for grey limestone of the Tiverskaya series, 2.3 °S and 338.4 °E for red beds of the Dniestrovskaya series, etc.) are well correlated with the Devonian segments of APWP for Baltica / Stable Europe. The same is true for the Silurian poles. The new results suggest that in the Ludlow, the East European platform was located at the near-equatorial latitudes of the Southern Hemisphere, and in the Pridoli, it moved to the north towards the equatorial latitudes of the Southern Hemisphere. Later on, the drifting mode was changed, and the platform moved to the south. In the Lochkovian, its position was stabilized at the equatorial latitudes of the Southern Hemisphere. Drifting of the platform can be described by counterclockwise rotation by 16° around the Euler pole (Φ=34 °S, Λ=247 °E).